AB0536 Can Rheumatologists Diagnose and Manage Giant Cell Arteritis Better than Non Rheumatologists. (15th July 2016) - Mercieca, C.; Galea, M.; Galea, R.; Borg, A.A.
Abstract : Background: Giant cell arteritis (GCA) is the commonest vasculitis affecting large and medium vessels. GCA presents with varying symptomatology which makes timely diagnosis and management challenging. A number of guidelines for the management of GCA have been published. 1, 2 In clinical practice, patients present to various specialists including general practitioners, general physicians, neurologists, rheumatologists and ophthalmologists which may result in wide variations in clinical care. Objectives: To establish the incidence of GCA in the Maltese population and whether rheumatologists are able to diagnose and manage giant cells arteritis better than non rheumatologists. Methods: This was a population observational study of Maltese patients between 2012 and mid 2015. All patients who underwent a temporal artery biopsy (TAB) were recruited and their case notes reviewed. Results: There were 122 patients (80 females) who underwent a TAB over 3.5 years for suspected GCA and out of these, 29 were positive. The incidence of biopsy proven temporal arteritis in Malta was 6.4 per 100, 000 inhabitants aged over 50 years. Mean age was 72.6 (SD 10.5) years. An additional 27 patients were treated for GCA on clinical grounds. Median CRP was 31 mg/L (IQR 6–87) and ESR 81 mm/hr (53.5–102.5). A total of 53 patients presented to the rheumatologists and 69 patients to non rheumatologists, and a positive TAB was obtained in 32% and 11.6% of patients respectively. Glucocorticoids were initiated before taking a TAB in 39.6% by rheumatologists and 34.7% and non rheumatologists. Overall (including TAB negative patients) 60.4% of patients presenting to the rheumatologists and 33% of patients presenting to non rheumatologists were treated as GCA. The starting dose of Prednisolone was between 40–60mg in 82% of rheumatologist treated patients compared to 65% by non rheumatologists. The tailoring regimes varied widely and documentation was poor for many patients treated by non rheumatologists. Rheumatologists treated 50% of patients with a Prednisolone dose of 40 mg or greater for at least a month, 37.5% were given lower doses while the treatment regimen was unclear in 12.5%. Non rheumatologists treated 20.8% with a Prednisolone dose of 40 mg or greater for at least a month, 33.3% were given lower doses and in 45.8% regimen was unclear. The main differential diagnoses were sepsis/infection (7 cases), PMR (4 cases), pyrexia of unknown origin (4 cases) and cluster headache (2 cases). Conclusions: Malta seems to have a low incidence of GCA comparable to other Mediterranean countries but lower than northern European countries. 3 GCA presents to a wide variety of specialists leading to a broad variation in treatment regimens. Non rheumatologists seem to have a lower threshold for TABs and possibly perform a number of unnecessary TABs. In order to ensure timely and appropriate management rheumatologists should take the lead and set up interspecialist pathways based on international guidelines that work in the local context. These pathways should include guidance about access, diagnosis, investigations and treatment and be disseminated to other clinical colleagues in both primary and secondary care. References: Mukhtyar C, et al. Ann Rheum Dis. 2009;68:318–23. Dasgupta B, et al. Rheumatology. 2010;49:1594–7. Mohammad AJ, et al. Ann Rheum Dis. 2015;74:993–7. Disclosure of Interest: None declared